Positive Psychological Interventions Helps Employees Work Stress - Journal, IMR (International Multidisciplinary Research Journal, 2014)
Stress is the emotional and physical strain caused by our response to pressure from the outside world. There are many stress full events in life an individuals and most of these stress events in life related to the workplace. Stress in the life of the organized workers consequently affects the health or behavior in organizations. Despite the preponderance of research describing the impact of stress in the workplace, few studies exist examining ways to reduce stress. The positive psychology is the scientific study of how humans achieve happiness and mental satisfaction. Positive psychology is based on the principal that all people want on the happy, fulfilled life. It is intended to build strength in a people to make the world a better place. Relaxation techniques is any method, process, procedure, or activity that helps a person to relax, to attain a state of increased calmness, or otherwise reduce levels of anxiety, stress or anger. The purpose of this research paper is to explore a positive psychology-based intervention such as relaxation techniques would actually reduce stress in the workplace. This paper emphasized on the relationship between stress and positive psychology through use some psychological intervention techniques.